1966
DOI: 10.1139/v66-340
|View full text |Cite
|
Sign up to set email alerts
|

The Reactions of the Disodium Adduct of Benzophenone Anil

Abstract: The disodium adduct of benzophenone anil has been treated with a variety of reagents, and the products have been isolated and identified. With alkyl halides, ethylene oxide, and diethyl sulfate, alkylation occurs a t the carbon atom. With tri-and tetra-methylene dibromide, nitrogen alkylation also occurs, thereby producing substituted pyrrolidine and piperidine derivatives. Benzaldehyde abstracts the allcali metal from the adduct whereas esters react to form the N-acyl derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1970
1970
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…On cooling and filtering, 5.5 g (79%) of N-benzoylbenzophenone imine was obtained. This material melted at 115-116 "C and did not depress the melting point of an authentic sample prepared by a published procedure (12).…”
Section: Reaction Of the Adduct Prepared From Two Equivalents Of Lithmentioning
confidence: 87%
“…On cooling and filtering, 5.5 g (79%) of N-benzoylbenzophenone imine was obtained. This material melted at 115-116 "C and did not depress the melting point of an authentic sample prepared by a published procedure (12).…”
Section: Reaction Of the Adduct Prepared From Two Equivalents Of Lithmentioning
confidence: 87%
“…Indeed, quenching such reduction mixtures with different alkyl halides provided evidence for the formation of an intermediate dianion (265); selected results are reported in Scheme 69 [149]. Interestingly, it was found that addition of t-BuOH (1 equiv) to dianion 265, followed by reaction with CH 3 I, allowed the regioselective synthesis of N-methyl-N-benzhydrylamine (268), a not surprising result since the anionic carbon should be more basic than an anionic nitrogen.…”
Section: Aryl Iminesmentioning
confidence: 99%
“…Interestingly, it was found that addition of t-BuOH (1 equiv) to dianion 265, followed by reaction with CH 3 I, allowed the regioselective synthesis of N-methyl-N-benzhydrylamine (268), a not surprising result since the anionic carbon should be more basic than an anionic nitrogen. However, quenching the same intermediate with benzoic esters or with diethylcarbonate led, quite surprisingly, to the formation of N-substituted reaction products 269, most probably as a result of steric hindrance at the carbanionic center; finally, reaction with benzaldehyde led to the recovery of the starting material (264), the corresponding amine (270), and a diastereoisomeric mixture of 1,2-diphenyl-1,2-ethanediol (251, Ar = Ph), thus suggesting an electron transfer process from dianion 265 to the aldehyde (Scheme 70) [149]. More recently, it was reported that reductive lithiation of phenone imines (271) with Li and a catalytic amount of C 10 H 8 , run in the presence of a carbonyl compound in THF at low temperature allowed, after aqueous work up, the synthesis of 1,2-aminoalcohols (272) in moderate yields (Scheme 71) [150].…”
Section: Aryl Iminesmentioning
confidence: 99%
“…Preparative-scale electrolysis of 12 in glyme or DMF afforded 9-anilinophenanthrene (13), with a yield of 60%. The elimination of an anilino fragment is an interesting process.…”
mentioning
confidence: 99%